Posidonomya (Bivalvia) from Northwest Peninsular Malaysia and its significance - Basir Jasin, (Universiti Kebangsaan Malaysia, 2015)
Posidonomya is common in the Kubang Pasu and Singa Formations in northwest Peninsular Malaysia. It was discovered from the red mudstone layers (redbeds) in many localities in Langkawi Islands, Perlis and Kedah. Previous studies suggested that the age of Posidonomya ranged from Middle Devonian to Carboniferous. Posidonomya beds in Kedah and Perlis are located above the Tournaisian radiolarian chert layers. The age of Posidonomya from Peninsular Malaysia is comparable to those of Europe, Morocco, Turkey and South China which range from Tournaisian to Serpukhovian, Early Carboniferous. The fossil specimens exhibit morphological features closely related to Posidonomya becheri Bronn. Two taxa were identified namely Posidonomya becheri Bronn and Posidonomya cf. kochi (von Koenen). The occurrence of Posidonomya indicates that the age of the lower part of the Kubang Pasu and Singa Formations is Early Carboniferous. Its geographic distribution formed a wide paleobiogeographic province in the Paleo-Tethys. The province was located in the warm tropical-subtropical climatic zone. Therefore, Posidonomya can be a good indicator for warm climate. Its wide distribution and short stratigraphic range make it a good index fossil for the Early Carboniferous.